Farmer for plantation palms in sub district Peranap, District Indragiri Hulu, Riau Province - sri rahmi utari (ISTORIA: Jurnal Pendidikan dan Sejarah, 2021)
This study examines the conflict between the community and oil palm plantation companies in Peranap District, Indragiri Hulu Regency, Riau. Conflicts occur due to community dissatisfaction with government policies and companies. Another cause is the expropriation of people's land by large plantations, which triggers community resistance. This writing uses the historical method with four stages, namely heuristics, source criticism, interpretation, histiography. In order to collect data, it is done by digging up information through interviews with perpetrators and witnesses of the history of oil palm plantation conflicts, besides collecting documents belonging to the company (notary deed), personal collections, Decree of the Regional Government of Indragiri Hulu Regency, then the data collected and conducted a process of criticism of sources internally and externally. The results of this study indicate that this conflict consists of external and internal factors. External factors, namely land grabbing, internal, namely the absence of the role and function of the cooperative. the presence of large companies has positive and negative impacts on society. The positive impact is the help of the community's economy, the lack of unemployment, the negative impact of the community losing land, and the promised plasma is not fulfilled.